Uji Komparatif Lapangan Jangka Pendek Produksi Energi Solar Photovoltaic Jenis Monocrystalline Dan Polycrystalline Pada Iklim Tropis - Tsabitul Khair; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Monocrystalline and polycrystalline are most widely used solar panels in Indonesia. This article discusses the energy production of both types with different tilted angles. The study was conducted by using 20 Wp solar panel. The tilted angles that examined in this research were 0, 15, 30 and 45 degree, respectively. The location of research was chosen at Faculty of Engineering building at Universitas Riau, Indonesia since it reflects the tropical weather condition. It has been found that monocrystalline produced higher energy compare with polycrystalline. The 0 and 15 degrees tilted angles gave the highest energy production of solar photovoltaic compare with the rest of tilted angles.Keyword: Monocrystalline, Polycrystalline, Solar Photovoltaic , Tilted Angle, Weather